Rancang Bangun Dashboard Informasi Covid-19 Dengan Metode RAD - Andri Cahyo Purnomo; Praditya Aliftiar; Yoga Darmawan (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
In 2019, a type of virus that is now known as COVID-19 (coronavirus diseases-19) was discovered. The virus found in Wuhan, China is a contagious virus that has claimed many lives. In Indonesia alone, cases of the COVID-19 virus (coronavirus diseases-19) were first confirmed in March 2020. The World Health Organization has determined that the COVID-19 virus (coronavirus diseases-19) is a pandemic on March 9, 2020. This has caused many people who are worried if they want to do activities outside the home. So a system is needed regarding the development of Covid-19, especially in Indonesia, to provide information and knowledge to the public so that it is hoped that it can prevent the transmission of the COVID-19 virus. Based on this background, the author will build an information dashboard that can be accessed by the public anywhere and anytime to see the development of Covid-19. By using the RAD (Rapid Application Development) method, it is hoped that later the system can be quickly built and used. In coding the program the author uses PHP as server-side with API integration from kawalcorona and HTML, CSS, Javascript as client-side. It is hoped that the system created will be used by the public as a reliable and accurate covid-19 information.